Pengaruh Literasi Keuangan dan Informasi Akuntansi terhadap Pengambilan Keputusan Investasi di Pasar Modal dengan Overconfidence sebagai Variabel Moderasi: Studi Kasus Generasi Z di Sumatera Barat - Muhammad Fauzan; Erly Mulyani (Universitas Negeri Padang, 2026)
This study investigates the influence of financial literacy and accounting information on investment decision-making among Generation Z in Indonesia’s capital market, with overconfidence as a moderating variable. The research aims to explain how financial understanding and the ability to interpret accounting data affect rational investment choices in a demographic known for high digital engagement and participation in financial activities. Using a quantitative method with an associative approach, data were collected from 190 respondents in West Sumatra through a structured questionnaire. The analysis was conducted using structural equation modeling. A key novelty of this research lies in the inclusion of accounting information as an independent variable alongside financial literacy, while testing overconfidence as a moderating variable—offering a different framework from previous studies that generally focus on direct relationships. The findings reveal that financial literacy and accounting information each have a significant positive influence on investment decisions. However, overconfidence did not moderate the relationship between these independent variables and investment decisions. These results suggest that while Generation Z investors possess sufficient knowledge and access to financial information, their psychological biases may not significantly alter their investment choices. The study concludes that financial education and transparency in accounting data are critical in shaping investment behavior. Future research is recommended to explore other psychological or behavioral moderators beyond overconfidence, as well as to expand the demographic and geographical scope to enhance generalizability.